2019
DOI: 10.1111/1758-2229.12727
|View full text |Cite
|
Sign up to set email alerts
|

Plant compartment and genetic variation drive microbiome composition in switchgrass roots

Abstract: SummarySwitchgrass (Panicum virgatum) is a promising biofuel crop native to the United States with genotypes that are adapted to a wide range of distinct ecosystems. Various plants have been shown to undergo symbioses with plant growth‐promoting bacteria and fungi, however, plant‐associated microbial communities of switchgrass have not been extensively studied to date. We present 16S ribosomal RNA gene and internal transcribed spacer (ITS) data of rhizosphere and root endosphere compartments of four switchgras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 52 publications
11
32
1
Order By: Relevance
“…Similarly, we found fewer reads on average in BFL vs. PKL RS and RE samples (Supplementary Figure S2). Alpha diversity analysis across samples from different Panicum species, ecotypes, and planting sites showed that RS microbial communities are generally more complex than RE communities (Figures 2A,B), which matched our expectations based on previous findings in switchgrass (Singer et al, 2018) and other host plants (Caporaso et al, 2010; Coleman-Derr et al, 2016; Wagner et al, 2016b). As microorganisms have to overcome plant immune defense mechanisms to inhabit the endosphere compartment, this generally leads to reduced complexity in the microbial community compared to respective surface communities, such as found in rhizosphere and phyllosphere (Schulz et al, 2006).…”
Section: Resultssupporting
confidence: 91%
“…Similarly, we found fewer reads on average in BFL vs. PKL RS and RE samples (Supplementary Figure S2). Alpha diversity analysis across samples from different Panicum species, ecotypes, and planting sites showed that RS microbial communities are generally more complex than RE communities (Figures 2A,B), which matched our expectations based on previous findings in switchgrass (Singer et al, 2018) and other host plants (Caporaso et al, 2010; Coleman-Derr et al, 2016; Wagner et al, 2016b). As microorganisms have to overcome plant immune defense mechanisms to inhabit the endosphere compartment, this generally leads to reduced complexity in the microbial community compared to respective surface communities, such as found in rhizosphere and phyllosphere (Schulz et al, 2006).…”
Section: Resultssupporting
confidence: 91%
“…In addition, our observations showed that the compartment had a limited effect on the response of fungal OTUs to B. papyrifera genotypes. These results are different from those of previous studies in switchgrass (41) and Populus (40). This difference could be attributed to two factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Strikingly different communities inhabit aboveground vs. belowground organs, the interior vs. exterior of an organ, and fine-scale spatial niches within organsdespite originating largely from the same pool of environmental microbes (Figure 1) (Zarraonaindia et al, 2015). Sample type or "compartment" consistently explains more microbiome variation than genotype or environment (Hamonts et al, 2018;Singer et al, 2019;Guo et al, 2021). Because a given pair of host genotypes might exhibit more phenotypic variation in one compartment than another, patterns of microbiome heritability can differ among plant parts.…”
Section: Microbiome Heritability Across Plant Anatomical Compartmentsmentioning
confidence: 99%